Kolmogorov Widths for Analogs of the Nikol’skii–Besov Classes with Logarithmic Smoothness - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish the exact-order estimates of Kolmogorov widths and entropy numbers for analogs of the Nikol’skii–Besov classes with logarithmic smoothness.